Initiating a text mining project for handling customer feedbacks analysis - Verneret, Alina (My University, 2022)
This research focuses on assessing the potential benefits related to implementing a text mining tool, inside the processes handling customer feedback analysis. This study will adopt both the perspectives of customers, and business, related to the processes of customer satisfaction reviews and analysis. The study has confirmed the following artifacts: 1. Text mining can leverage the use of customer unstructured text data. 2. Text mining can help optimizing some internal processes. 3. Co-creation of value can create new sources of knowledge flows across the organization and enhance the customer experience. Text mining has the potential to subsequently optimize both the processes, and the customer experience as a whole.
Keywords: Text mining, Natural Language Processes, CSAT surveys